Gene Signatures and Prognostic Values of m6A RNA Methylation Regulators in Ovarian Cancer - Han, Xiao; Liu, Jie; Cheng, Guomei; Cui, Shihong (Cancer control, 2020)
Background: N6-methyladenosine (m6A) is the most common form of mRNA modification under the field of “RNA epigenetics.” However, its role in ovarian cancer (OC) development is poorly understood. In the current study, we aimed to identify gene signatures and prognostic values of m6A RNA methylation regulators. Method: Specifically, we downloaded Mutations and Copy number variant (CNV) data from the TCGA database for 579 OC patients, then analyzed gene expression and prognosis value using integrative bioinformatics. Thereafter, we verified the related biological processes of Wilms’ tumor 1-associating protein (WTAP) gene using Gene set enrichment analysis (GSEA). Results: Results showed that almost all ovarian cancer patients (99.31%) have CNVs with at least 1 m6A regulatory gene, whereas 83.76% of cases exhibited concurrence of CNVs in more than 4 m6A regulatory genes. Additionally, alteration of m6A regulators was associated with historical grade, whereas integrative bioinformatics and Cox multivariate model analysis revealed a significant correlation between high WTAP expression and worse ovarian cancer outcomes. Moreover, GSEA revealed that high WTAP expression was associated with cell cycle regulation and MYC targets. Conclusion: Overall, our findings demonstrate the significance of high-frequency genetic alterations of m6A RNA methylation regulators and WTAP’s poor prognosis value in OC. These findings provide valuable insights into the role of m6A methylation in OC, and will be vital in guiding development of novel treatment therapies.